1998
DOI: 10.1038/bjc.1998.97
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression and phosphorylation of β-catenin in human colorectal cancer

Abstract: The cytoplasmic domain of cadherins is known to associate with the intracellular proteins, catenins, which link cadherins to the actin-based cytoskeleton. In this study, we immunohistochemically investigated the expression of beta-catenin as well as E-cadherin and alpha-catenin in 86 human colorectal cancers, and we analysed their coexpression pattern and relationship to clinicopathological factors. In cancerous tissues, the frequency of reduced expression of beta-catenin (28 of 86, 33%) was similar to that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
54
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 36 publications
(33 reference statements)
4
54
2
Order By: Relevance
“…Similar alterations of ␤-catenin staining were seen in the UC-related and sporadic colorectal cancers. A decrease in membranous ␤-catenin expression and increases in cytoplasmic and nuclear ␤-catenin expression were observed in the UCrelated cancers, similar to that seen elsewhere in sporadic colorectal cancers (1,11). The increase in nuclear expression, however, was less frequent in the UC-related (48%) than in the sporadic tumors (81%).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Similar alterations of ␤-catenin staining were seen in the UC-related and sporadic colorectal cancers. A decrease in membranous ␤-catenin expression and increases in cytoplasmic and nuclear ␤-catenin expression were observed in the UCrelated cancers, similar to that seen elsewhere in sporadic colorectal cancers (1,11). The increase in nuclear expression, however, was less frequent in the UC-related (48%) than in the sporadic tumors (81%).…”
Section: Discussionmentioning
confidence: 66%
“…Alterations of ␤-catenin expression are likely to affect both of these functions (18). ␤-catenin expression is frequently altered in sporadic colorectal cancers (1,2,7,11,19), whereas very little is known about its expression in UC-related cancers. In this study, immunohistochemistry was used to define the expression of ␤-catenin, and its two binding partners E-cadherin and APC, in UC-related colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent work has confirmed that tyrosine phosphorylation of β-catenin may participate in regulation of the cadherin-catenin complex in vivo (Takayama et al, 1998). Abnormal expression of each of the main components of the complex (E-cadherin, α-, β-catenin and plakoglobin) have been demonstrated in gastric cancer, and are commoner in the diffuse, poorly differentiated than in the intestinal, more well-differentiated histological type (Jawahari et al, 1997).…”
mentioning
confidence: 95%
“…Possible risk factors for lymph node metastasis in submucosal invasive colorectal carcinoma include the depth of submucosal invasion, poorly differentiated histology, lymphatic vessel invasion, expression of vascular endothelial growth factor-A and -C, and expression of β-catenin (Takayama et al 1998;Maeda et al 2003;Kojima et al 2005;Walgenbach-Bruenagel et al 2006;Liang et al 2006;Saad et al 2006;Kaneko et al 2007a;Ishii et al 2009). Several studies have reported that tumor budding is a histological risk factor for lymph node metastasis of colorectal carcinoma (Hori et al 2005;Park et al 2005;Masaki et al 2006;Kaneko et al 2007b).…”
mentioning
confidence: 99%